Anti-inflammatory Effect of the Hydroethanolic Extract from Dacryodes kukachkana Leaves in Mice: Role of Macrophage Nitric Oxide - Anny Beatriz Silveira Peixoto; Bianca Feitosa Holanda; Cléo Vanessa Gomes de Queiroz; Roberta de Freitas Lopes; Diego Freitas de Araujo; Lucas Soares Frota; Sara Ingrid Caetano Gomes Barbosa; Selene Maia de Morais; Renildo Moura da Cunha; Ana Maria Sampaio Assreuy (Archives of Current Research International, 2024)
Aims: This study aimed to characterize and evaluate the effect of the hydroethanolic extract from D. kukachkana leaves (HEDkL) in mice models of acute inflammation and in isolated macrophages stimulated with carrageenan, along with possible adverse effects in the central nervous system. Study Design: After characterization of phenolic constituents, HEDkL was injected in the animals 60 min before the administration of inflammatory stimulis. The anti-inflammatory effect of HEDkL was evaluated in the models of paw edema, peritonitis and air pouch and in peritoneal macrophages stimulated with carrageenan in vitro. The per se effect of HEDkL was evaluated for behavioral alterations. Place and Duration of Study: Higher Institute of Biomedical Sciences and Animal Health Research Center, State University of Ceara; Physiopharmacology Laboratory, Federal University of Acre; between March 2021 and March 2023. Methodology: The characterization of phenolic compounds was performed by HPLC-DAD. Swiss mice (25 - 35 g) received HEDkL (25 - 200 mg/kg; per oral) 60 min before carrageenan. Macrophages were incubated with HEDkL (100 - 200 µg/mL) before being stimulated. The anti-inflammatory effect was assessed for edema, hypernociception, vascular permeability, leukocyte infiltrate, oxidative stress and inflammatory. Behavioral alterations (exploratory, anxiolytic, depressant activities) were evaluated in the animals treated with HEDkL (50 mg/kg). Results: The HPLC-DAD revealed the presence of ellagic acid, epicatechin and gallic acid. In the paw edema model, HEDkL (50 mg/kg) inhibited the edema late phase (2 - 5h) by 45% and the activity of the enzyme myeloperoxidase by 48%. In the peritonitis model, HEDkL (50 mg/kg) reduced leukocyte migration (45%), hypernociception (73%), total proteins (20%) and NO2-/NO3- (23%). In the air pouch model, HEDkL (50 mg/kg) reduced the migration of total leukocytes (76%) and neutrophils (88%). In vitro HEDkL (200 µg/mL) reduced by 31% the NO2-/NO3- in the supernatant of macrophages. HEDkL did not alter the animals exploratory, anxiolytic, or depressant behaviors. Conclusion: HEDkL containing flavonoids and phenols presents anti-inflammatory effect in vivo and in vitro involving nitric oxide inhibition, being devoid of behavioral alterations.